Al-Mushakalah in Prophetic Hadith - M., M. Amer Hamad Ghadeer (International Journal of Psychosocial Rehabilitation, 2020)
This study examines Al-Mushakalah [representing homophones, polysemys, and homonyms in English] in prophetic Hadith. The study is divided into two sections. The first section includes the lexical and technical definition of the term Al-Mushakalah. The second section introduces samples of Al-Mushakalah in the Prophet’s Hadith. This study is not a statistical research of Mushakalah in the Hadith, but it just sheds light on some models.